2018
DOI: 10.1021/acs.est.8b01947
|View full text |Cite
|
Sign up to set email alerts
|

Field-Scale Heterogeneity and Geochemical Regulation of Arsenic, Iron, Lead, and Sulfur Bioavailability in Paddy Soil

Abstract: A method using miniaturized arrayed DGT-probes (PADDI) for high-frequency in situ sampling with LA-ICPMS and CID analysis was developed to measure the field-scale heterogeneity of trace-element bioavailability. Robust calibrations (R2 > 0.99) combined with high-sensitivity (LOD = 0.35 ng cm–2), multielemental detection, and short measurement times were achieved using a new LA-ICPMS microDGT analysis. In the studied paddy-site (size: ∼2500 m2), total element concentrations across the field were approximately un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Even though Fe oxides can provide sorption sites for various cation elements, Cu has been reported to be preferentially absorbed by organic matter, such as humic substance. Regarding As, Fe (hydr)­oxides were the dominant reactive adsorption surface for As, but the disconnection between As and Fe has also been revealed in some previous studies that have shown that both porewater and DGT measurements of Fe and As were not significantly correlated in some paddy fields and laboratory tests. , This does not necessarily discount the importance of reductive dissolution of Fe in As mobilization, but it does highlight the importance of other factors, such as DOC and microorganism diversity, as controls for As mobilization dynamics. , …”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Even though Fe oxides can provide sorption sites for various cation elements, Cu has been reported to be preferentially absorbed by organic matter, such as humic substance. Regarding As, Fe (hydr)­oxides were the dominant reactive adsorption surface for As, but the disconnection between As and Fe has also been revealed in some previous studies that have shown that both porewater and DGT measurements of Fe and As were not significantly correlated in some paddy fields and laboratory tests. , This does not necessarily discount the importance of reductive dissolution of Fe in As mobilization, but it does highlight the importance of other factors, such as DOC and microorganism diversity, as controls for As mobilization dynamics. , …”
Section: Resultsmentioning
confidence: 87%
“…The laser was set up first with primary calibrations using the National Institute of Standards and Technology (NIST) glass standard 610. The LA-ICPMS system was optimized principally by adjusting gas flow rates, torch sampling depth, and radio frequency (RF) power to achieve the maximum signal intensity and stability of target elements while minimizing interferences . The instrumental parameters for analysis are listed in Table S3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the ploughed paddy topsoil does begin the cropping cycle relatively homogenized, but after flooding and overtime (0-4 months) the spatial diversity of the system increases greatly. 33 These initial first steps in solute interchange and soil surface interactions created by the emergent rhizospheres of the newly planted rice, are important because they create zones of localized enrichment/depletion in elemental bioavailability, forming different ecological niches (Figure 1), thus impacting plant uptake through diffusion and resupply. However, these gradients in porewater elements availability, later develop/establish into chemically stratified zones differing with more permanency in their solid phase composition and stoichiometry, such as is the case with Fe or Mn plaque aggregation.…”
Section: Solid-water Partitioning Contributes To Metals Mobility the Results From Dgtmentioning
confidence: 99%
“…The diffusive gradients in thin-films (DGT) technique is an alternative and very well established passive sampler; it is based on Fick’s first law of diffusion and was originally invented for measuring inorganic substances in situ without field calibration. DGT samplers can enrich the target analytes in situ, avoiding the potential errors caused by sample transportation and pretreatment of grab sampling. The measured data integrate exposure concentrations over the sampling time to provide a time-weighted average (TWA) concentration.…”
Section: Introductionmentioning
confidence: 99%